Impact of Supportive Leadership During Covid-19 on Nurses' Well-Being: The Mediating Role of Psychological Capital - Um-e-Rubbab,; Farid, Tahir; Iqbal, Sadaf; Saeed, Imran; Irfan, Shahid; Akhtar, Tanvir (Frontiers in Psychology, 2021)
The corona virus disease (Covid-19) has significantly affected the social, physical and psychological health of workers specifically the nurses working in the healthcare sectors. Studies have been conducted on the impact of Covid-19 on employee’s well-being, organizational structure and job design; however limited studies have been conducted focusing on the impact of leadership on employee’s well-being during Covid-19 pandemic. Drawing on job demands-resources model and social exchange theory, we examined the impact of supportive leadership on employee’s physical, social and psychological well-being during the Covid-19 pandemic. In addition, we examined the mediating role of psychological capital in examining the relationship between supportive leadership, employee’s physical, social and psychological wellbeing. Based on three-wave time-lagged design the data were collected from 214 nurses linear regression analysis and Hayes Process for mediation was used to test the proposed hypothesis. As hypothesized supportive leadership predicted employee’s physical, social and psychological well-being. In addition, psychological capital mediated the relationship between supportive leadership, employee’s physical, social and psychological well-being. Implications for research, theory, and practice are discussed.